Hands-on parallel programming with C# 8 and .NET Core 3 : build solid enterprise software suing task parallelism and multithreading - Tanwar, Shakti (Packt Publishing, 2019)
Hands-On Parallel Programming with C# 8 and .NET Core 3 presents a smart way of learning and implementing parallel programming concepts. The book details threading and concurrency fundamentals that will help any C# developer build optimized applications.